Improving Physician Communication With Patients as Measured by HCAHPS Using a Standardized Communication Model. (November 2017) - Horton, Devin J.; Yarbrough, Peter M.; Wanner, Nathan; Murphy, Ryan D.; Kukhareva, Polina V.; Kawamoto, Kensaku
Physicians often fail to communicate well with patients. The objective of this retrospective controlled interrupted time series study was to evaluate the impact of a standardized communication intervention to improve physician communication. All patients ages 18 years or older (N = 7739 visits) admitted to University of Utah Health Care in Salt Lake City, Utah, from July 1, 2012, to June 31, 2014, were included. Obstetrics, rehabilitation, and psychiatric patients were excluded. The primary outcome was the percentage of patients who answered "Always" to all HCAHPS questions regarding physician-patient communication. Among the intervention group, the primary outcome increased from 56% to 63% ( P = .014, N = 1021) while remaining stable for the control group (65% to 66%, P = .6, N = 6718). The downward trend reversed after the intervention (−0.6% to +1.7% per month, P < .001). Standardized communication was associated with improvement in physician communication HCAHPS scores.